UV‐activated hydrosilylation of (Me‐Cp)Pt(Me)3: Enhanced photocatalytic activity, polymerization kinetics, and photolithography. Issue 47 (12th July 2019) - Xi, Lu; Liu, Zhu; Su, Jiahui; Bei, Yiling; Xiang, Hongping; Liu, Xiaoxuan
ABSTRACT: Hydrosilylation is commonly known as a thermally induced addition reaction between unsaturated bonds and SiH bonds to synthesize or crosslink organosilanes and organosilicones, while it has emerged that it can also be activated under the coaction of UV irradiation and specific platinum catalyst. For higher photopolymerization conversion, excessive platinum catalyst is always required; however, this inevitably causes the significant increase of production cost and decrease of operation time. In this study, traces of trimethyl(methylcyclopentadienyl) platinum (IV) (Me‐Cp)Pt(Me)3 catalysts is combined with different photosensitizers (PSs) to efficiently promote the UV‐activated hydrosilylation. Naphthalene is found to be the most applicable PS, because it improves the photopolymerization conversion from about 70 to 100% for the crosslinking of silicone rubbers. This UV‐activated hydrosilylation is more likely to follow the first‐order reaction kinetics, and its activation energy is 30.9 kJ mol −1 . The mechanical properties and thermostability of UV‐crosslinked silicone rubbers are also enhanced with the incorporation of naphthalene. Moreover, this UV‐activated hydrosilylation of silicone rubbers reveals a potential role to prepare complicated geometry shapes by photolithography. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48251. Abstract : The cover picture shows that the photosensitizer‐mediated energy transmission from UV light to platinum catalyst makes UV‐activated hydrosilylation of silicone rubber better conversion and crosslinking network.